KEBIJAKAN HUKUM PIDANA TERHADAP PERILAKU PENGUSAHA DALAM PRODUKSI, PENYIMPANAN DAN PENJUALAN OBAT-OBATAN TANPA KEAHLIAN DAN KEWENANGAN - WIDIARTO PURWOTO, EKO, SOPONYONO (Diponegoro Law Journal, 2012)
The circulation of Counterfeit medicines more increase, it’s be influence Pharmacy industry and Producer too. The composition in the market can be harmfully because of Many consumed, include generic and counterfeit The recht staat Policies research in producer behavior to produce, warehouse and sell of medicine without expert and authority have 2 problems:  Criminal Law Policies in restrict the  producer  behavior  to  produce,  warehouse  and  sell  of  medicine  without  expert  and authority at present? Criminal Law Policies  in restrict the producer behavior to produce, warehouse and sell of medicine without expert and authority at the next? Writer  do  researching  with  Empiric  juridical  approach  methode,  Empiric  yuridis approach   method   is  procedures  to  solve  problem  with  second  information,  Primary information in the fact, dan Task of Badan POM in protect Consumer medicine product is law in action and the effects of changes producer can be restrict abuse of consumer  law ( Nomor 8 Tahun  1999) Can be Concluded as Criminal Law Policy into the producer behavior to  produce, warehouse and sell of medicine without expert and authority can be feel Ineffective becaus imprisonment sentenced. Make  less with the applied Criminal Law Policies of producer behavior   can round up who ‘s product as in law the code of conducts as the rules